Dividend payout among Nigerian firms: Do female directors matters? - Adamu Adamu Idris; Rokiah Ishak; Nor Laili Hassan (Jurnal Ekonomi Modernisasi, 2019)
This study explores how female director(s) affect the decision to pay dividend in the sub-Saharan Africa. The study specifically employs non-financial firms listed on the Nigerian Stock Exchange Market from 2009-2015 and logit regression as the technique for data analysis. The independent variable of interest in the study is female director. Consistent with the hypothesis, the study found strong association that firms with at least one female director on board are more likely to affect the payment of dividends. The findings subsist after the commencement of the 2011 CCG and when firms with negative earnings were excluded from the main sample. Furthermore, the results do not change when the model was re-estimated using an alternative measure of female director as well as using OLS regression.